57 Effects of Diploid and Tetraploid Annual Ryegrass Cultivars on Cattle Performance, Herbage Mass, and Nutritive Value. (28th November 2020) - Montgomery, Sarah M; Karisch, Brandi; Parish, Jane A; Morrison, Jesse; Baldwin, Brian
Abstract: Annual ryegrass (Lolium multiflorum Lam.) can be divided into two cytotypes: diploid (2n = 2x) and tetraploid (2n = 4x). Polyploid versions of a given plant species result in increased seedling vigor, more robust growth and, potentially, greater yield. While most data suggest no difference in yield between diploid and tetraploid cultivars, there is still potential for weight gain advantages thanks to increased non-structural carbohydrates in tetraploid cells. The objectives of this study were to compare weight gain of cattle grazing either diploid or tetraploid cultivars of annual ryegrass. Two diploid annual ryegrass cultivars (Marshall and Tam 90) and two tetraploid cultivars (Jumbo and Nelson) were planted in 0.81-ha pastures, each replicated four times. Four steers (mean initial BW = 214 kg) were randomly assigned to each pasture for an 82-d grazing period. Body weights were recorded starting at d0 then every 28 days throughout the season. Data were analyzed in the GLM procedure of SAS using a significance level of α = 0.05. There were significant differences between cytotypes with respect to seasonal yield with diploids (9547.90 kg/ha) yielding greater than tetraploids (7762.00 kg/ha). As expected, ADF and NDF fractions were significantly less for tetraploids (ADF; 31.39%, NDF; 31.39%) compared to diploids (ADF; 33.75%, NDF; 53.25%). Tetraploids also contained significantly greater crude protein (13.50%) than diploids (12.90%). Cytotype had no effect on final average daily gain (ADG) (P = 0.9427). However, final ADG was significantly impacted by cultivar (P = 0.0134). Final ADG for Tam 90 (1.10 kg/d) was greater than Marshall (0.92 kg/d). Cattle grazing Nelson (1.04 kg/d) and Jumbo (0.99 kg/d) did not differ. Results show that regardless of differences in seasonal yield and nutritive value between cytotypes, there were no advantages in ADG for cattle grazing either cytotype.